Holding Public Procurement Socially Accountable: The Adoption of the Integrity Pact Approach and the Role of the Independent Observers. (4th May 2022) - Prateeppornnarong, Dhiyathad
Abstract: Having been introduced in 2015 by the efforts of the elite-backed civil society organization – the Anti-Corruption Organization of Thailand (ACT) – the Integrity Pact (IP) approach, calling for citizen engagement in exacting accountability in the public procurement system, is claimed to have been producing promising results for prevention of corruption in Thailand's public procurement. This paper critically explores the IP approach adopted in Thailand with a particular emphasis on the role of the Independent Observers (IOs). The objectives are threefold: to examine the arrangements of Thailand's IP approach and the IOs; to identify the contribution of the IP approach to the prevention of corruption in Thailand's public procurement; and to investigate fundamental challenges the IP approach and the IOs face. The findings demonstrate that the IP approach is an effective means for ensuring citizen engagement in exacting public accountability and prevention of corruption in public procurement. However, they also highlight the key challenges of effective implementation of the approach including politicization of the IOs, the exclusion of the IOs in the drafting of Terms of Reference (TOR) and the officials' misconceptions about the IOs.